Perlindungan Hukum Terhadap Hak-Hak Anak dan PerempuanPasca Perceraian - Aris Priyadi (Faculty of Law, Universitas Wijayakusuma Purwokerto, 2021)
In general, it can be said that it is the will of the people who carry out the marriage, that the marriagewill continue and only be interrupted when one of the husbands or wives dies. But in reality, maintaining ahappy and eternal family is not easy. In the course of the household, there are often problems that resultin disputes and quarrels. When the rights of one party are violated, or one of the parties does not carryout their obligations, there will be turmoil in the household. Many husbands and wives finally decide to endtheir marriage by divorce. Divorce has legal consequences both for ex-husbands and ex-wives and forchildren. The Marriage Law does not provide a clear description if there is a dispute or struggle for childcustody (hadhanah), then custody of the child is given to the father or mother. However, the Compilationof Islamic Law (KHI) provides a more detailed description of child custody or hadhanah. Based onArticle 105 in conjunction with Article 156 of the Compilation of Islamic Law (KHI).